The Effectiveness of The Recommendations Of The Integrated Assessment Team (TAT) of The National Narcotics Agency of Bali Province as A Judge's Consideration In Granting Drug Case Decisions - Ni Wayan Indri Astuti; Ni Ketut Wiratni; I Made Mulyawan Subawa (Return : Study of Management, Economic and Bussines, 2024)
This study aims to analyze the procedure and effectiveness of the recommendations provided by the Integrated Assessment Team (TAT) of the National Narcotics Agency of Bali Province in determining rehabilitation for narcotics abusers. The research employs a normative legal method, incorporating a statute approach, case approach, and conceptual approach. The findings indicate that the TAT, consisting of a legal and medical team, conducts assessments to provide rehabilitation recommendations for narcotics abusers. The recommendations serve as evidence in court to help judges decide on rehabilitation for narcotics abusers, victims, and addicts. The research, which analyzed 10 narcotics cases, reveals that in 9 cases, the judges considered TAT’s recommendations when issuing their verdicts. However, the judges' decisions did not always align with the content of the recommendations. This demonstrates that while the TAT's recommendations are effective in influencing judicial decisions, full alignment between recommendations and verdicts is not guaranteed. The study concludes with a suggestion for stronger inter-agency commitment to ensure that TAT’s recommendations are consistently applied in legal proceedings. Additionally, it proposes the inclusion of norms related to integrated assessments in future revisions of Indonesia's Narcotics Law.